Contamination and screening level toxicity of sediments from remediated and unremediated wetlands near Sydney, Australia - Ying, G.; Rawson, Christopher; Kookana, R.; Peng, P.; Warne, M.; Tremblay, L.; Laginestra, E.; Chapman, J.; Lim, R. (Society of Toxicology and Chemistry (SETAC), 2009)
The present study assessed contamination and toxicity of sediments from seven remediated and remnant wetland sites within Sydney Olympic Park, Australia, and four unremediated sites adjacent to its boundary using chemical analysis and a luminescent bacterial biosensor assay (Escherichia coli). Concentrations of metals (Pb, Cr, Cu, Ni, Zn, Cd, and As) and persistent organic chemicals (DDT and its metabolites, dichlorodiphenyldichloroethane and dichlorodiphenyldichloroethylene; polycyclic aromatic hydrocarbons; polychlorinated biphenyls; and polychlorinated dibenzo-p-dioxins and dibenzofurans) in sediments and their pore-water samples were determined. Zinc concentrations were the highest of the metals in the sediments (84-618 mg/kg), and at eight sites, metal concentrations in sediments exceeded the Australian ecological trigger values for Pb, Zn, and Ni. Concentrations of organic contaminants in the sediments exceeded the trigger values at all 11 sites for DDTs, at 6 sites for polycyclic aromatic hydrocarbons, and 5 sites for polychlorinated biphenyls. Sediment samples from the four unremediated sites outside the Sydney Olympic Park had dioxin concentrations greater than 200 pg (toxic equivalency per gram). The same four sites were identified as contaminated in pore-water toxicity tests with the luminescent biosensor, generally consistent with the bioavailable fractions of the contaminants (pore-water and Tenax extraction data), as well as dioxin levels, in the sediments. Preliminary toxicity identification and evaluation tests of the pore water from the four sites outside the park demonstrated that organic contaminants were the main cause of toxicity to E. coli, with no evidence that metals contributed to the toxicity of the pore water.